The Mitigating Role of Trait Core Confidence on Psychological Distress in Entrepreneurship. Issue 3 (5th June 2020) - Sergent, Kayla; Lee, Dongseop; Stajkovic, Alexander D.; Greenwald, Jessica M.; Younger, Shannon; Raffiee, Joe
Abstract : We conceptualize the mitigating role of trait core confidence on psychological distress in entrepreneurship manifested by occupational stress, anxiety, and depression. To facilitate field research, we first developed a short trait core confidence scale and validated it in six independent samples ( N = 2, 434). To test our hypothesis that trait core confidence negatively relates to base‐line levels of psychological distress as well as reduces fluctuations of distress in entrepreneurship, we collected data from a 3‐day entrepreneurial event called Startup Weekend across seven occasions in the United States. High trait core confidence was related to lower psychological distress both at the start of the event on Friday and at the end of it on Sunday. Core confidence remained stable from Friday to Sunday, as well as 1 month following the event, affirming its trait properties. Additionally, we measured team confidence during the event and found that high team confidence reduced psychological distress of team members. This research contributes to the research on the role of dispositions in occupational health psychology and to a better understanding of how distress of aspiring entrepreneurs is mitigated by trait core confidence.